2019
DOI: 10.1177/0197918319830695
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Turkish and Moroccan Belgians toward Redistribution and Government Responsibility: The Role of Perceived Discrimination, Generation, and Religious Involvement

Abstract: This article contributes to the debate about migration’s impact on welfare state support by investigating the welfare opinions of migrants and their descendants. It examines whether experiences of group and individual discrimination explain the welfare attitudes of this group over and beyond classical predictors of self-interest and political ideology. Using survey data from Belgian citizens of Turkish and Moroccan descent, we show that stronger support for redistribution is associated with higher levels of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 84 publications
(148 reference statements)
2
8
0
Order By: Relevance
“…The role of national and ethnic identification should, however, not be overestimated given the size of the standardized parameters and the relative importance of other predictors such as perceptions of group discrimination, religious involvement and the generation to which people belong. Consistent with previous research (Galle et al, 2019), Belgian citizens of Turkish or Moroccan descent with higher levels of perceived group discrimination are more in favour of redistribution (β = 0.205; p = 0.000) and compared to strictly practising Muslims, those who are non-strictly practising are less egalitarian (β = –0.203; p = 0.000). While the model estimated with the distinct measures for national and ethnic identification illustrates a significant positive effect of belonging to the second rather than first generation on support for redistribution (β = 0.174; p = 0.033), this effect is no longer significant (β = 0.150; p = 0.071) in the second model with combined identity categories.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The role of national and ethnic identification should, however, not be overestimated given the size of the standardized parameters and the relative importance of other predictors such as perceptions of group discrimination, religious involvement and the generation to which people belong. Consistent with previous research (Galle et al, 2019), Belgian citizens of Turkish or Moroccan descent with higher levels of perceived group discrimination are more in favour of redistribution (β = 0.205; p = 0.000) and compared to strictly practising Muslims, those who are non-strictly practising are less egalitarian (β = –0.203; p = 0.000). While the model estimated with the distinct measures for national and ethnic identification illustrates a significant positive effect of belonging to the second rather than first generation on support for redistribution (β = 0.174; p = 0.033), this effect is no longer significant (β = 0.150; p = 0.071) in the second model with combined identity categories.…”
Section: Resultssupporting
confidence: 88%
“…Perceived group discrimination was found to be related to a greater willingness to challenge income inequality and to greater support for redistribution. Furthermore, the study originally confirmed the positive association between religiosity and welfare support that has been studied within populations with Protestant, Catholic or secular denominations (Ervasti, 2012), among Muslim minorities living in Europe (Galle et al, 2019). A strong religious involvement suggests the endorsement of the Islamic visions of a just socioeconomic order with a strong emphasis on reducing the gap between rich and poor (Dean and Khan, 1997).…”
Section: Determinants Of Ethnic Minorities’ Attitudes Towards Redistrsupporting
confidence: 56%
See 1 more Smart Citation
“…Particularly, during the COVID-19 crisis, the issue of trust in governments is highly important and vital (He, Ma 2021;Mansoor 2021). Over time, citizens' trust in positive actions has been assessed by the government (Galle et al 2020).…”
Section: Compatibility and Efforts For Increasing The Qol And Sopmentioning
confidence: 99%
“…A major crisis can be a crucial moment for consolidating governments’ political status quo. When a government announces measures in the best interests of the public, the trust among citizens changes positively ( Yousaf et al, 2016 ; Galle et al, 2020 ). A government’s decisions in emergency situations, such as stay-at-home orders, free medical facilities, and financial assistance, will increase the public’s trust in government, especially when the government gives a strong response.…”
Section: Introductionmentioning
confidence: 99%